Pengaruh Persepsi Jamaah Terhadap Pemahaman Agama Jamaah Sholat Jum’at dimasjid AL-Hijri 2 - Muhammad Mursyid; Hasan Basri Tanjung; Ahmad Kamaluddin (Universitas Pahlawan Tuanku Tambusai, 2022)
Prayer is a liaison between a servant and his god and has a position like the head in Islam, Friday prayer is a two raka'at fard prayer which is carried out on Friday and is done at dzuhur time after two sermons, the sermon is one of the legal requirements from Friday worship is obligatory on male believers who are puberty. Friday sermon is also a series of activities that cannot be separated from the implementation of Friday prayers as a whole. The purpose of this study was to determine whether there was an influence of the perception of the congregation of Al-Hijri 2 mosque on the understanding of the congregation's religion. This study uses a quantitative approach. This study uses a quantitative approach. The population is all congregations of Friday prayers at AL-Hijri 2 mosque, totaling 500 people. Sampling is done by purposive sampling, which is a determination technique with certain considerations. The data were analyzed using the product moment correlation test. The results showed that there was a significant influence between the congregation's perception of the sermon material and the congregation's religious understanding after listening to the Friday sermon. Keywords: Congregational Perception, Religious Understanding, Friday Sermon